Persepolis 2 [book club bag] - Satrapi, Marjane, 1969- (Pantheon Books, 2004)
The great-granddaughter of Iran's last emperor and the daughter of ardent Marxists continues her description of growing up in Tehran--a country plagued by political upheaval and vast contradictions between public and private life.